Antimicrobial activity of actinomycetes and characterization of actinomycin-producing strain KRG-1 isolated from Karoo, South Africa (Brazilian Journal of Pharmaceutical Sciences, 2019)
In the present study we reported the antimicrobial activity of actinomycetes isolated from aridic soil sample collected in Karoo, South Africa. Eighty-six actinomycete strains were isolated and purified, out of them thirty-four morphologically different strains were tested for antimicrobial activity. Among 35 isolates, 10 (28.57%)showed both antibacterial and antifungal activity. The ethyl acetate extract of strain KRG-1 showed the strongest antimicrobial activity and therefore was selected for further investigation. The almost complete nucleotide sequence of the 16S rRNA gene as well as distinctive matrix-assisted laser desorption/ionization-time-of-flight/mass spectrometry (MALDI-TOF/MS) profile of whole-cell proteins acquired for strain KRG-1 led to the identification of Streptomyces antibioticus KRG-1 (GenBank accession number: KX827270). The ethyl acetate extract of KRG-1 was fractionated by HPLC method against the most suppressed bacterium Staphylococcus aureus (Newman). LC//MS analysis led to the identification of the active peak that exhibited UV-VIS maxima at 442 nm and the ESI-HRMS spectrum showing the prominent ion clusters for [M-H2O+H]+ at m/z 635.3109 and for [M+Na]+ at m/z 1269.6148. This information could be assigned to chromopeptide lactone antibiotic - actinomycin. Our results suggest that unexplored soils could be an interesting source for exploring antibacterial secondary metabolites.